ANALISIS PENGETAHUAN DAN TINGKAT KECEMASAN KAUM IBU DALAM MENYIKAPI PANDEMI COVID-19 DI KOTA BANDA ACEH - Andhika Jaya Putra; Risjki Apridawati (Jurnal Anifa: Studi Gender dan Anak, 2022)
Covid-19 is a contagious disease and can result in death. This disease is a disease that has spread throughout the world. The purpose of this study is to see how knowledge and anxiety levels are and the factors that influence people's knowledge and levels of anxiety in responding to the Covid-19 pandemic outbreak in Banda Aceh City. This type of research uses descriptive qualitative and data collection techniques using observation, interviews and documentation, and descriptive analysis. The findings of this study are that the knowledge of mothers in Banda Aceh City is quite good about the dangers of covid-19 so that it has an impact on reducing the level of anxiety about Covid-19. In addition, mothers in Banda Aceh City are pretty good at following health protocols such as wearing masks, stealing hands with soap in running water, and the high participation of mothers in Aceh in carrying out COVID-19 vaccinations.